1994
DOI: 10.1017/s0031182000078549
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relatedness as a determinant of predisposition to Ascaris lumbricoides and Trichuris trichiura infection

Abstract: The present study examines the role of host genetics in predisposition to Ascaris lumbricoides and Trichuris trichiura infection, by comparing the associations between age-standardized infection intensities of parents and their children (genetically related), with age-standardized infection intensities of parents alone (not related), within families previously demonstrated to exhibit familial predisposition. The lack of a consistent trend in infection intensity associations within families, in particular the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 13 publications
2
25
1
1
Order By: Relevance
“…In contrast with previous work in which exposure to infection appeared to mask the influence of host genetic factors on predisposition [83], Williams-Blangero et al [56,60,61] clearly demonstrated a role for host genetics in determining infection intensity. In their most recent paper, Williams-Blangero and colleagues concluded that efforts will now focus on the characterisation of the specific genes underlying the three significant QTL regions that have been identified [61].…”
Section: Future Directions and Considerationscontrasting
confidence: 82%
“…In contrast with previous work in which exposure to infection appeared to mask the influence of host genetic factors on predisposition [83], Williams-Blangero et al [56,60,61] clearly demonstrated a role for host genetics in determining infection intensity. In their most recent paper, Williams-Blangero and colleagues concluded that efforts will now focus on the characterisation of the specific genes underlying the three significant QTL regions that have been identified [61].…”
Section: Future Directions and Considerationscontrasting
confidence: 82%
“…Often a minority of a population will produce large amounts of eggs indicating heavy infection, while the majority will have light infection and produce very few eggs (Palmer & Bundy 1995). There is also a familial aggregation and predisposition to Ascaris and Trichuris infections (Chan et al 1994a), which does not appear to be genetically determined but may be more strongly determined by environmental and behavioral factors (Chan et al 1994b).…”
Section: Discussionmentioning
confidence: 99%
“…However Chan et al [41] noted that environmental or behavioural features of the family household were found to be a major determinant of infection status. Nevertheless,…”
Section: Accepted Manuscriptmentioning
confidence: 99%